Hypertensive patients in hospital practice: comparative characteristics of patients with and without 24-hour blood pressure monitoring data - T. S. Ilyina; V. M. Gorbunov; M. M. Lukyanov; Ya. N. Koshelyaevskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To study the features of 24-hour ambulatory blood pressure (BP) monitoring (ABPM) in patients with hypertension (HTN) and comorbid pathologies within the hospital registry of a multidisciplinary medical center.Material and methods. The study was carried out within the GARANT hospital registry. This registry included 5781 patients. The HTN in the electronic patient record was revealed in 4725 (81,7%) patients (age 65,5±11,3 years, men 51,7%). Of these, ABPM was performed in 16,8% of patients (HTN+ABPM), 83,2% were in the comparison group (HTN without ABPM). The characteristics of patients in these groups were compared and ABPM feasibility was assessed.Results. In the HTN+ABPM group compared with the HTN without ABPM group, the mean age of patients was 63,9±13,9 vs 65,8±10,7 (p<0,01), women — 59,1 vs 46,1% (p<0,01), the mean number of cardiovascular diseases — 2,15±1,16 vs 2,68±1,16 (p<0,01), the mean number of non-cardiac diseases — 2,92±1,35 vs 2, 61±1,37 (p<0,01), office systolic and diastolic BP — 146,7±22,1/83,9±11,6 vs 136,9±19,7/79,2±10,4 mm Hg (p<0,01), respectively. The predominant blood pressure phenotype in the HTN+ABPM group is white coat hypertension (including during treatment) (49,2%). According to linear regression, the white coat effect is significantly positively associated with age, female sex, and negatively associated with prior myocardial infarction.Conclusion. The GARANT registry results revealed that in-hospital ABPM was more often performed on younger people, mainly women, with less severe cardiovascular multimorbidity. These patients were characterized by a higher level of office BP upon admission to hospital and a higher prevalence of HTN as the only cardiovascular disease. Carrying out ABPM in patients included in the registry seems justified.